Compact microsecond pulsed magnetic field generator for application in bioelectronics - Novickij, V.; Grainys, A.; Novickij, J.; Lucinskis, A.; Zapolskis, P. (Elektronika ir Elektrotechnika, 2013)
High power pulsed magnetic field generator for application in the bioelectronics area has been developed. The developed magnetic field facility is capable of generating pulsed magnetic field up to 5 T with pulse width in the microsecond range. The maximum repetitive frequency of the pulses is 40 Hz. The generator has been implemented by application of three high power thyristor switches, capacitor bank, specifically designed load coil with crowbar diode and the control circuitry. The inductive coil that has an integrated cuvette with effective volume of 2.4 μl for biological samples is presented in the study. The control algorithm of the circuitry is also overviewed in this work. Finite element analysis of the generated pulsed magnetic field and comparison to the acquired experimental pulse are performed. Potential application of the generator in the bioelectronics area of magnetoporation is discussed. Based on the results further development and improvement ways of the facility for better integration in the area of bioelectronics are proposed. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.3266